Jenis Ikan Dominan, Kontinyuitas Penjualan dan Penetapan Harga Ikan pada Pasar Pengecer di Kodya Ambon dan Maluku Tengah - Bernard B. de Rosari; Abdul Choliq (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1997)
IndonesianA research has been done to see the dominant fish sold, the continuity of fish supply, and the influence of the quantity of certain fish sold and prices of the other fish to the fish selling price determinant at retailing markets in Ambon and Central Maluku. Three markets were chosen, they were Pasar Rumah Tiga, Pasar Lama Ambon and Pasar Binaya Masohi, Central Maluku. Survey method was used in the research. Time series data were collected every three weeks from September 1995 to March 1996. The results showed, that the dominant type of fish sold continously in Pasar Rumah Tiga were Scads, Frigate tuna,